KOMUNIKATOR TUNARUNGU DAN TUNANETRA - Syahrul Syahrul; Mochamad Fajar Wicaksono (CCIT Journal, 2012)
This paper describes the design and implementation of the deaf and blind communicator with the aim that they can communicate by using a Braille Codes per character and speech recognition using a computer. Communicator device is designed using AT89C51 microcontroller to change the characters that is sent by the computer into Braille code. The signal transmitted from the computer by hearing impairment through RS-232 serial interface with the help of driver IC ULN2803 to drive the solenoid. The end of the solenoid form a pattern of Braille code. Speech pattern recognition used are dictation mode with discrete speech method, whole word, large vocabulary and speaker dependent is designed with SAPI 5.1, Microsoft Speech Engine SDK 5.1 and Delphi software 6.0 to create an application program. On testing who performed indicate that the all the characters that is sent from keyboard can be converted become Braille Character who represented through the solenoid. While the recognition of sound patterns of the microphone most of the well can be translated into the characters displayed on a computer monitor. The success rate in speech recognition can be influenced by several factors such as differences in the sound at the time of training and at the time of dictation, noise from the environment and the quality of the microphone being used.